Low-dimensional nanomaterials as an emerging platform for cancer diagnosis and therapy - Cui, Fengzhi; Liu, Jianhua; Zhang, Tianqi; Pang, Siwen; Yu, Haijia; Xu, Nannan (Frontiers in Bioengineering and Biotechnology, 2023)
The burden of cancer is burgeoning and increasing, widely recognized as one of the main death reasons for the human being. Despite tremendous efforts have been made worldwide to stem progression and metastasis of cancer, the morbidity and mortality in malignant tumors have been obviously rising and threatening human health. In recent years, nanomedicine becomes a newborn strength gradually to occupy a considerably important position in precision oncotherapy, which improves the diagnosis, treatment, and long-term prognosis of cancer. In particular, LDNs with distinctive physicochemical capabilities have provided great potential for advanced biomedical applications attributed to their large surface area, abundant surface binding sites, and good cellular permeation property. In addition, LDNs could integrate CT/MR/US/PAI and PTT/PDT/CDT/NDDS into a multimodal theranostic nanoplatform achieving targeted therapy and efficacy assessments for cancer. This review attempts to concisely summarize the classification and major properties of LDNs. Simultaneously, we particular emphasis on its applications in imaging, diagnosis and treatment of cancerous diseases.